Cyclic behavior of channel-encased braces incorporating round HSS - Seker, Onur; Shen, Jay; Faytarouni, Mahmoud; Akbas, Bulent; Shen, Xiaopu; Zhang, Hanming; Li, Peizhe (Structures (Oxford), 2023)
Bracings made with cold-formed round hollow structural shapes (HSS) are commonly utilized in ductile concentrically braced frames (CBFs) in seismic regions for their efficiency in terms of high load-bearing capacity and ease of construction. Bracings are expected to sustain a ductility demand that ranges between 10 and 20 without fracture when ductile CBFs subject to severe earthquake ground motions. However, the experimental findings accentuate that ductile braces, even those with round HSS that possess impractically small diameter-to-wall thickness ratios (D/t), are prone to premature fracture. Thus, developing a simple and cost-effective performance-enhancing system for existing conventional CBFs incorporating round HSS could be imperative to mitigate the potential seismic risk. For this purpose, an existing round HSS is encased in two channels to form a buckling-controlling mechanism that is expected to improve the seismic hysteretic behavior, consequently, the energy dissipation capacity of ductile braces. Experimental and parametric numerical studies have been conducted to comprehend the level of improvement in the cyclic behavior and the impact of geometric parameters (i.e., slenderness and D/t ratios). The overarching results indicate that channel-encased bracing improves the seismic hysteretic behavior, yielding a stable and symmetric cyclic response. In addition, the results suggest that the optimal design parameters, including gap amplitude and encasing thickness, play a critical role in achieving desired ductility level.